To simplify the expression \(38 \cdot 33\) using the Product Rule of Exponents, we can apply the rule which states that when multiplying two expressions with the same base, we add their exponents.
In this case, both terms have the base \(3\). We can rewrite the expression as follows:
\[ 38 \cdot 33 = 3^8 \cdot 3^3 \]
According to the Product Rule of Exponents:
\[ a^m \cdot a^n = a^{m+n} \]
We can now add the exponents:
\[ 3^8 \cdot 3^3 = 3^{8+3} = 3^{11} \]
Thus, the simplified expression is:
\[ 3^{11} \]